THE IMPROVEMENT OF TRUTH, JUSTICE, DIVERSITY, AND HUMAN DIGNITY VALUES TROUGH PPKMB PROGRAM ON PHYSICS EDUCATION STUDENTS - Paul Suparno (Sanata Dharma University Yogyakarta, 2017)
Sanata Dharma University Physics students are supposed to improve Sanata Dharma main values: truth, justice, diversity, and human dignity. The improvement is done through PPKMB program, a character building program in one semester. This research wants to see whether this program succeeded or not. The research used 42 physics students as sample. The PPKMB program is used as a treatment. The research applied some instruments such as questionnaires, field notes, and student report on their project. Data were analyzed quantitatively and qualitatively. The results show that the truth, justice, and diversity values improved, the human dignity value was not significantly different, and according to the students this program was useful and successful.DOI: https://doi.org/10.24071/ijiet.2017.010207